The Politics of Moderate Islam in Indonesia: Between International Pressure and Domestic Contestations - Alvian, Rizky Alif; Ardhani, Irfan (Al-Jami'ah Research Centre, 2023)
This article focuses on understanding how Muslim-majority countries adapt to the discourse of moderate Islam to their political circumstances. Using Indonesia’s experience as a case study, the article argues that countries’ political configurations influence decisions to apply the discourse in domestic politics. In the Indonesian context, political leaders’ unwillingness and inability to confront the Islamists are crucial factors that limited the influence of moderation discourse in former Presidents Megawati’s and Yudhoyono’s reigns. During that period, the presidents used the discourse mainly to signal to the international community that Indonesia did not align itself with the transnational network of terrorism. In contrast with his predecessors, President Widodo is willing to use the discourse to undermine the influence of the Islamists, thereby neutralising their challenges and cementing his political power. Moreover, this article demonstrates that the content of the discourse of moderation is indeterminate. Although the concept is usually associated with positive democratic attitudes, Widodo’s emphasis on support for national unity in his definition of moderation shows that political actors can appropriate the concept and adjust it to their particular political needs. [Tulisan ini berusaha memahami bagaimana negara mayoritas Muslim beradaptasi dengan wacana Islam moderat dalam kehidupan politiknya. Menggunakan pengalaman Indonesia sebagai studi kasus, tulisan ini berpendapat bahwa keputusan untuk menerapkan wacana tersebut dalam politik domestik dipengaruhi oleh konfigurasi politik dalam negeri. Dalam konteks Indonesia, ketidakinginan dan ketidakmampuan para pemimpin politik untuk menghadapi kelompok Islamis adalah faktor krusial yang membatasi pengaruh wacana moderasi di masa kepemimpinan Presiden Megawati dan Yudhoyono. Dalam periode tersebut, kedua presiden menggunakan wacana moderasi utamanya untuk mengirim sinyal kepada komunitas internasional bahwa Indonesia tidak berpihak pada jaringan teroris transnasional. Berbeda dengan pendahulunya, Presiden Widodo memanfaatkan wacana tersebut untuk melemahkan pengaruh kelompok Islamis, dalam rangka menetralisir tantangan dan mengukuhkan kekuatan politiknya. Lebih dari itu, tulisan ini menunjukkan bahwa isi dari wacana moderasi tidaklah pasti. Walaupun konsep tersebut umumnya diasosiasikan dengan sikap demokratik yang positif, penekanan Widodo pada dukungan bagi persatuan bangsa dalam definisi moderasinya menunjukkan bahwa para aktor politik dapat menyesuaikannya dengan kepentingan politik mereka yang spesifik.]